Contemporary Speculations and Insightful Thoughts on Buckwheat—A Functional Pseudocereal as a Smart Biologically Active Supplement - Vladimir S. Kurćubić; Slaviša B. Stajić; Vladimir Jakovljević; Vladimir Živković; Nikola Stanišić; Pavle Z. Mašković; Vesna Matejić; Luka V. Kurćubić (Foods, 2024)
Today, food scientists are interested in more rational use of crops that possess desirable nutritional properties, and buckwheat is one of the functional pseudocereals that represents a rich source of bioactive compounds (BACs) and nutrients, phytochemicals, antimicrobial (AM) agents and antioxidants (AOs), which can be effectively applied in the prevention of malnutrition and celiac disease and treatment of various important health problems. There is ample evidence of the high potential of buckwheat consumption in various forms (food, dietary supplements, home remedies or alone, or in synergy with pharmaceutical drugs) with concrete benefits for human health. Contamination as well as other side-effects of all the aforementioned forms for application in different ways in humans must be seriously considered. This review paper presents an overview of the most important recent research related to buckwheat bioactive compounds (BACs), highlighting their various functions and proven positive effects on human health.